Outcome after percutaneous coronary intervention with contemporary stents in patients with concomitant peripheral arterial disease: A patient-level pooled analysis of four randomized trials. (August 2022) - Pinxterhuis, Tineke H.; Ploumen, Eline H.; Zocca, Paolo; Doggen, Carine J.M.; Schotborgh, Carl E.; Anthonio, Rutger L.; Roguin, Ariel; Danse, Peter W.; Benit, Edouard; Aminian, Adel; Stoel, Martin G.; Linssen, Gerard C.M.; et al.
Abstract: Background and aims: A considerable number of patients who undergo percutaneous coronary intervention (PCI) also have peripheral arterial disease (PAD) – a signal of more advanced atherosclerosis. After bare metal and early-generation drug-eluting coronary stent implantation, PAD patients showed inferior outcome. As stents and medical treatment were further improved, we aimed to assess the impact of PAD on outcome of PCI with contemporary new-generation stents. Methods: We analyzed 3-year pooled patient-level data from 4 large-scale randomized new-generation stent trials to compare all-comer patients with and without (core lab-verified) history of symptomatic PAD, defined as obstructive lesions in peripheral locations including lower and upper extremities, carotid, vertebral, mesenteric and renal arteries. Main endpoint was target vessel failure: cardiac death, target vessel-related myocardial infarction, or clinically indicated target vessel revascularization. Results: Of all 9204 patients, 695 (7.6%) had a history of symptomatic PAD. They were older and had more often diabetes, renal failure, hypertension, hypercholesterolemia, and prior stroke. PAD was an independent risk factor for target vessel failure (adjusted-HR:1.42, 95%-CI:1.12–1.73, p  = 0.001). Target vessel revascularization (adjusted-HR:1.37, 95%-CI:1.04–1.80, p  = 0.026), death (adjusted-HR:1.52, 95%-CI:1.17–1.99, p  = 0.002), and major adverse cardiovascular event risks (adjusted-HR:1.36, 95%-CI:1.13–1.64, p  = 0.001) were also substantially higher. Conclusions: A history of symptomatic PAD still allows to simply identify patients with increased risk of unfavorable clinical outcome after PCI, including a higher risk of repeated coronary revascularization, despite using contemporary stents. In clinical practice, this knowledge about higher event risks of PAD patients is helpful both during Heart Team discussions and when informing patients about the procedural risk. Graphical abstract: Image 1 Highlights: Patients with peripheral arterial disease have higher complication risks after percutaneous coronary intervention (PCI). Peripheral arterial disease also increases the risk of repeated revascularization. In addition, all-cause mortality and major adverse cardiac event risks are higher. Yet, the adverse event rates are much lower as compared to historical controls.